-10(-3h-2)-10(-2h-9)=

Simple and best practice solution for -10(-3h-2)-10(-2h-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(-3h-2)-10(-2h-9)= equation:


Simplifying
-10(-3h + -2) + -10(-2h + -9) = 0

Reorder the terms:
-10(-2 + -3h) + -10(-2h + -9) = 0
(-2 * -10 + -3h * -10) + -10(-2h + -9) = 0
(20 + 30h) + -10(-2h + -9) = 0

Reorder the terms:
20 + 30h + -10(-9 + -2h) = 0
20 + 30h + (-9 * -10 + -2h * -10) = 0
20 + 30h + (90 + 20h) = 0

Reorder the terms:
20 + 90 + 30h + 20h = 0

Combine like terms: 20 + 90 = 110
110 + 30h + 20h = 0

Combine like terms: 30h + 20h = 50h
110 + 50h = 0

Solving
110 + 50h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-110' to each side of the equation.
110 + -110 + 50h = 0 + -110

Combine like terms: 110 + -110 = 0
0 + 50h = 0 + -110
50h = 0 + -110

Combine like terms: 0 + -110 = -110
50h = -110

Divide each side by '50'.
h = -2.2

Simplifying
h = -2.2

See similar equations:

| -8.4(x-2.75)=25.2 | | -6(4-8s)=20 | | 6.4x-3.5=52.2 | | F+v-e=2fore | | 1.6=-0.3 | | 7y+4x-2=0 | | .073x+.0127(12000-x)=1308 | | 25500+2000=47900-800 | | 9=0+0 | | 34+a=62 | | -3x-1=-10x-8 | | 4xy^4z^3-4xy^4z^3= | | M-56=10 | | 12x-8=-308 | | -5(t-3)-(t+1)=3 | | 7k+10-15-4K=-13 | | h+14=33 | | 9x-6=4x+1 | | 2500=x^4 | | 0.5(4z+7)+17.7=0.7(4z-4) | | 6x-2+3x=4x-3+4x | | 17-3m=8 | | 3x+8+2=19 | | 28+h=44 | | 35x-1=20x+2 | | 66x+4=-2 | | (8x-12)=6x+8 | | -2x^2-9x+35=0 | | 19+4h=1-5k | | log[2](5x-2)=1 | | (4x-20)x=90 | | 3f+8+4=-23 |

Equations solver categories